Improvement student learning achievement using the integration of the NHT model with Jigsaw on geometry topic - Khikmah Kurnia; Supriyono Supriyono; Rintis Rizkia Pangestika (Prodi PGMI IAIN Salatiga, 2021)
This study aims to describe the increase in student learning achievement using the integration of the NHT model with the Jigsaw on geometry topic. The subjects were students of class V elementary school 2 Seren, Purworejo, Central Java. The research variables used were student achievement and the integration of the NHT model with the Jigsaw. Meanwhile, the research instrument used teacher observation sheets and evaluation of student achievement. The data analysis technique in this study used descriptive quantitative data analysis techniques. The results showed that in the first cycle there were 60% of students had finished learning. Meanwhile, as many as 40% of students have not finished learning. Therefore, it can be concluded that the average score of students in the first cycle was 64, 1. Then in the second cycle, 80% of the students who had to achieve the passing score were obtained. Meanwhile, as many as 20% of students have not finished studying. Therefore, it can be concluded that there has been an increase in student achievement, namely as much as 80% of students have achieved the success indicator, namely 75%. Therefore, it can be concluded that the integration of the NHT model with Jigsaw can improve student achievement in building material for semester 2 in class V elementary school 2 Seren Academic Year 2019/2020.